Agility and lean in the supply chain in manufacturing SMEs: a review of the literature - Cueva Quiroz, Oscar Edinson (2023)
In a competitive world with constant changes, it is crucial that manufacturing companies look for new strategies to apply in their supply chain in order to generate a competitive advantage and be sustainable over time. The application of the agile methodology together with lean in the supply chain, seek to provide a solution to this problem. The purpose of this study is to perform a systematic review of the last 5 years on agility and lean in the supply chain in manufacturing SMEs. Also, to analyze and identify the main factors to increase agility along with the application of lean methodology. Consequently, it was important to review a considerable number of articles and authors specialized in these topics, as well as to be updated of the changes that are due to the course of time. Therefore, through the PRISMA method, 122 articles were obtained from the Scopus database, between the years 2017 and 2021, for subsequent analysis and to achieve the objective of the research. With this study, it is sought that manufacturing companies around the world begin to investigate more about this strategy and seek its application, to become highly competitive companies.